Сорняк, обвивший сумку палача - Брэдли Алан (Флавия де Люс ведет расследование, 2017)
Экземпляры: ЦБ (20171213) / Инвентарный номер: 49687 / Цена: 238.00 / Сис.шифр: 84(4Вел) / Авт.знак: Б 89 / ГРНТИ: 17 / ББК: 84(4Вел)